2021
DOI: 10.37028/lingcure.v5n1.45
|View full text |Cite
|
Sign up to set email alerts
|

Political language variation: stylistic based study

Abstract: This study aimed at finding out the figures of speech used by the government in the political language variation and the purposes to which they serve. On the basis of the data analysis, it was found that there are sixteen types of figures of speech contained in the political language variation, for example, euphemism, repetition, parallelism, personification, parable, anticlimax, sarcasm, trope, hyperbole, pleonasm, climax, antithesis, synecdoche, anaphor, allusion, and metonymy. The purposes of their uses are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Antiglobalization mythology is first of all aimed at counteracting the myth of unity on the metaphysical plane, as well as at influencing collective consciousness and transforming the matrix of individual behavior (Putrayasa, 2021;Woodlove & Vurly, 2017). Affecting changes in political consciousness, myths of difference, as well as myths of unity, lead to the embodiment of mythological ideas and thought constructs in the space of reality.…”
Section: Discussionmentioning
confidence: 99%
“…Antiglobalization mythology is first of all aimed at counteracting the myth of unity on the metaphysical plane, as well as at influencing collective consciousness and transforming the matrix of individual behavior (Putrayasa, 2021;Woodlove & Vurly, 2017). Affecting changes in political consciousness, myths of difference, as well as myths of unity, lead to the embodiment of mythological ideas and thought constructs in the space of reality.…”
Section: Discussionmentioning
confidence: 99%
“…The dialectical method of ascent from the abstract to the specific was used to identify the general laws of political life development. The methods of formal logic were used to study the eventual manifestations of the political (Ching & Chan, 2020;Putrayasa, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, parents may consider teaching a baby a second language too early, as studies have shown that learning a second language at an early age is much easier. It is easier for a child to learn two languages at the same time than for an adult to try to learn a second language later in life (Putrayasa, 2021;Schweizer et al, 2012).…”
Section: Methodsmentioning
confidence: 99%